Detection of Autoantibodies Against Actin Filaments in Celiac Disease. Issue 1 (4th January 2013) - Porcelli, B.; Ferretti, F.; Vindigni, C.; Scapellato, C.; Terzuoli, L.
<x xml:space="preserve">Abstract</x> Introduction Serum autoantibodies specifically directed toward intracellular cytoskeletal actin filaments (anti‐actin antibodies, AAA) were found to be associated with intestinal villous atrophy (IVA) in celiac disease (CD). The aim of this study was to assess IgA‐AAA with a commercial test that uses sections of rat intestinal epithelial cells in a well‐selected cohort of patients and to evaluate the relationship between the presence of serum IgA‐AAA and the severity of intestinal mucosa damage. J. Clin. Lab. Anal. 27:21–26, 2013. © 2012 Wiley Periodicals, Inc. Materials and Methods Serum samples from 70 CD patients and 150 controls subjects were analyzed retrospectively for the presence of IgA‐AAA. Results The indirect immunofluorescence test that we used has a specificity of 100%; the sensitivity of the test is not high (25.7%). In this study we also show that serum AAA are more frequently positive in CD patients with total IVA (77.8%) and that this association is significant Discussion IgA‐AAA certainly cannot take the place of much more sensitive tests such as a‐tTG and EMA in the diagnosis of CD because of their low sensitivity; nonetheless, these antibodies could be determined in a‐tTG and/or EMA positive patients who cannot undergo an intestinal biopsy because of a severe contraindication, or in the case of negative consensus regarding endoscopy, or when the histology interpretation is difficult. Conclusion In conclusion, the IFI commercial test with intestinal epithelial cells as substrate offers a useful method for IgA‐AAA determination. Serum IgA‐AAA positivity is indicative of more severe intestinal histology damage and their assay could be a real help to the clinician, especially in the complicated cases.